Intra-cyclic speed fluctuations of uni-lateral arm amputee front crawl swimmers - Payton, C.; Wilcox, C. (Biomechanics and Medicine in Swimming X, 2006)
Front crawl swimmers with an arm amputation at elbow level are deprived of an important propelling surface. The purpose of this study was to determine the extent to which unilateral arm amputee front crawl swimmers are able to generate swimming speed with their sound and with their affected limbs. Eight trained swimmers (2 male, 6 female) performed front crawl trials (without a leg-kick) at middle distance pace, while attached to a velocity meter (100 Hz). Trials were simultaneously videotaped underwater. Mean intra-cyclic speed fluctuation was 35 ± 5% of the mean swimming speed. Peak swimming speed achieved during the push phase of the sound limb (1.30 ± 0.17 m.s-1) was significantly higher than that found during the push phase of the affected limb (1.14 ± 0.11 m.s-1). This indicates that the swimmers were able to use their affected limb to increase their swimming speed, but not as effectively as with their sound limb.